2022
DOI: 10.1002/jbm.b.35072
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid cross‐linked chitosan for inhibiting oxidative stress after nerve injury

Abstract: Scaffold design is particularly important and necessary for soft tissue repair such as nerve tissue repair. In this article, we designed and manufactured a macroporous chitosan‐based hydrogel with excellent cell compatibility and antioxidant properties. Here, the chitosan (CS) based hydrogel is obtained by repeated freezing and thawing using citric acid (CA) as a cross‐linking agent. We have evaluated the effects of citric acid content on the physical and chemical properties of hydrogels through mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…This can be attributed to the presence of citric acid, which was incorporated as a primary crosslinker during the fabrication of the hydrogel. The free radical scavenging activity of citric acid has been reported previously when it was used as a crosslinker to prepare chitosan hydrogels. , Therefore, we are able to conclude that our dual crosslinked PVA/NC hydrogels had better antioxidant activity than the neat PVA hydrogel.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This can be attributed to the presence of citric acid, which was incorporated as a primary crosslinker during the fabrication of the hydrogel. The free radical scavenging activity of citric acid has been reported previously when it was used as a crosslinker to prepare chitosan hydrogels. , Therefore, we are able to conclude that our dual crosslinked PVA/NC hydrogels had better antioxidant activity than the neat PVA hydrogel.…”
Section: Resultssupporting
confidence: 76%
“…We suspect the antioxidant property displayed by the neat PVA is due to the presence of citric acid. It has been previously reported that citric acid can neutralize ROS by the direct transfer of hydrogen atoms. In the case of the PVA/NC hydrogels, we observed significantly lower fluorescence intensities in all of the PVA/NC hydrogels compared to the neat PVA hydrogel control and the H 2 O 2 -treated cell control at both days 1 and 7. The observed reduction in the fluorescence intensity is proposed to have been caused by the combination of (i) the presence of citric acid in the hydrogels and (ii) the release of NC from the hydrogels.…”
Section: Resultssupporting
confidence: 54%
“…The band at 1419 cm −1 is the bending vibration of C–H 2 , the band at 1091 cm −1 is the absorption of C–O, and the band at 844 cm −1 is the absorption peak of C–C. The characteristic bands of CA are the wide band of O–H stretching vibrations at 3428 cm −1 and the –COOH stretching of C=O at 1727 cm −1 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, chitosan grafted polyethylene glycol or temperature response chain to become a water-soluble thermal response polymer, forming gel at physiological temperature. 33 However, the dissolution and solubility of chitosan have close relation to the acetylation rate of itself. Alkalization of chitosan solution to pH value similar to physiological environment will lead to the formation of gel precipitation, which restricted the research and application of chitosan in cell embedding.…”
Section: Chitosanmentioning
confidence: 99%
“…Iron crosslinking is usually achieved by chemical ring method. For example, chitosan grafted polyethylene glycol or temperature response chain to become a water‐soluble thermal response polymer, forming gel at physiological temperature 33 . However, the dissolution and solubility of chitosan have close relation to the acetylation rate of itself.…”
Section: Natural Polymer‐based Cell Encapsulation Headingmentioning
confidence: 99%